Franklin MacVeagh papers - MacVeagh, Franklin, 1837-1934.
Correspondence; memoranda; speeches; writings; subject files; business, legal, and financial records; family papers; autobiographical material; newspaper clippings; scrapbook; printed matter; and other papers relating primarily to MacVeagh's service as U.S. secretary of the treasury under President William H. Taft and to MacVeagh's roles as Chicago businessman, banker, civic reformer, patron of the arts, and politician. Includes materials pertaining to the MacVeagh (McVey) and Eames families, Chicago social and civic affairs, and Franklin MacVeagh & Company, a wholesale grocery business. Subjects include the anthracite coal strike in Pennsylvania, 1902; election of 1896; political patronage; the silver question; and the U.S. Customs Service and U.S. Internal Revenue Service during the Taft administration. Organizations represented include American Civic Association, Art Institute of Chicago, Chicago Bureau of Charities, Chicago Literary Club, Chicago Symphony Orchestra, Civic Federation of Chicago (Ill.), Immigration Restriction League (U.S.), Municipal Art League of Chicago, National Civic Federation, National Civil Service Reform League (U.S.), U.S. Bureau of Engraving and Printing, U.S. President's Commission on Economy and Efficiency, U.S. Public Health Service, and U.S. Tariff Board.
Family correspondents include MacVeagh's wife, Emily Eames MacVeagh; his son, Eames MacVeagh; and his brother, Wayne MacVeagh. Other correspondents include Charles Francis Adams, R.O. Bailey, Richard Achilles Ballinger, Henry C. Bannard, James J. Barbour, Henry Sherman Boutell, William S. Broughton, Daniel Hudson Burnham, Royal Eubank Cabell, Walter T. Chandler, George B. Cortelyou, Shelby M. Cullom, J.M. Dickinson, Walter L. Fisher, Francis, E. Frothingham, S.M. Gaines, John Hay, Frank H. Hitchcock, Rollin Arthur Keyes, Philander C. Knox, George R. Leighton, Carl Lumholtz, Thomas S. Lynch, George Washington Maher, Lee McClung, Charles H. Miller, Charles P. Montgomery, Lawrence O. Murray, Charles Nagel, Charles Dyer Norton, Whitelaw Reid, Eliza Ruhamah Scidmore, Henry L. Stimson, William H. Taft, George W. Wickersham, Leonard Wood, and members of the Pumpelly family.
Library of Congress Prints and Photographs Division.
Library of Congress Geography and Map Division.
Lawyer, businessman, and U.S. secretary of the treasury.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Charles Francis, -- 1835-1915 -- Correspondence; Bailey, R. O. -- Correspondence; Ballinger, Richard Achilles, -- 1858-1922 -- Correspondence; Bannard, Henry C. -- Correspondence; Barbour, James J. -- 1869- -- Correspondence; Boutell, Henry Sherman, -- 1856-1926 -- Correspondence; Broughton, William S., -- 1874-1951 -- Correspondence; Burnham, Daniel Hudson, -- 1846-1912 -- Correspondence; Cabell, Royal Eubank, -- 1878-1950 -- Correspondence; Chandler, Walter T. -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Cullom, Shelby M. -- 1829-1914 -- Correspondence; Dickinson, J. M. -- 1851-1928 -- Correspondence; Fisher, Walter L. -- 1862-1935 -- Correspondence; Frothingham, Francis E. -- Correspondence; Gaines, S. M. -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Hitchcock, Frank H. -- 1867-1935 -- Correspondence; Keyes, Rollin Arthur, -- 1854-1925 -- Correspondence; Knox, Philander C. -- 1853-1921 -- Correspondence; Leighton, George R. -- Correspondence; Lumholtz, Carl, -- 1851-1922 -- Correspondence..; Lynch, Thomas S. -- Correspondence; MacVeagh, Eames, -- 1871- -- Correspondence; MacVeagh, Emily Eames -- Correspondence; MacVeagh, Wayne, -- 1833-1917 -- Correspondence; Maher, George Washington, -- 1864-1926 -- Correspondence; McClung, Lee, -- 1870-1914 -- Correspondence; Miller, Charles H. -- Correspondence; Montgomery, Charles P. -- Correspondence; Murray, Lawrence O., -- 1864-1926 -- Correspondence..; Nagel, Charles, -- 1849-1940 -- Correspondence; Norton, Charles Dyer, -- 1871-1922 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Scidmore, Eliza Ruhamah, -- 1856-1928 -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; Taft, William H. -- 1857-1930.; Taft, William H. -- 1857-1930 -- Correspondence; Wickersham, George W. -- 1858-1936 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Eames family; MacVeagh family; McVey family; Pumpelly family -- Correspondence; United States. -- Bureau of Engraving and Printing; United States. -- Department of the Treasury. -- Office of the Secretary; United States. -- Internal Revenue Service; United States. -- President's Commission on Economy and Efficiency; United States. -- Public Health Service; United States. -- Tariff Board; American Civic Association; Art Institute of Chicago; Chicago Bureau of Charities; Chicago Literary Club; Chicago Symphony Orchestra; Civic Federation of Chicago (Ill.); Franklin MacVeagh & Company; Immigration Restriction League (U.S.); Municipal Art League of Chicago; National Civic Federation